2021
DOI: 10.3389/fpls.2021.647585
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Among Phenotypic Parameters Related to the Growth and Photosynthesis of Strawberry (Fragaria × ananassa Duch.) Grown Under Various Light Intensity Conditions

Abstract: The objective of this study was to investigate characteristics of phenotypic parameters such as physiology, yield, and fruit quality responses of strawberry (Fragaria × ananassa Duch.) to various light intensity conditions (VLICs), and to determine the correlations among these phenotypic parameters. Strawberry plants were cultivated in a smart greenhouse separated into four areas, three of which were completely shaded by curtains from 20:00 until 10:00 (3 hS), 12:00 (5 hS), and 14:00 (7 hS), respectively. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
5
8
0
Order By: Relevance
“…Under shading conditions, plants might maintain the original photosynthetic rate by changing photosynthetic pigment contents and chl a/b ratio or adapt to low light by reducing the photosynthetic rate [3,28]. In this study, compared with no shading, the chlorophyll and carotenoid contents in shaded leaves increased significantly at the later stage, while the chl a/b ratio decreased, which was consistent with the reports of strawberry and rice [2,29]. The results indicated that shaded jujube leaves obtained higher light energy by increasing photosynthetic pigment contents and meanwhile improved photosynthetic phosphorylation activity by reducing the chl a/b ratio [30,31].…”
Section: Shading Increased Photosynthetic Pigment Contents Of Leaves ...supporting
confidence: 91%
See 4 more Smart Citations
“…Under shading conditions, plants might maintain the original photosynthetic rate by changing photosynthetic pigment contents and chl a/b ratio or adapt to low light by reducing the photosynthetic rate [3,28]. In this study, compared with no shading, the chlorophyll and carotenoid contents in shaded leaves increased significantly at the later stage, while the chl a/b ratio decreased, which was consistent with the reports of strawberry and rice [2,29]. The results indicated that shaded jujube leaves obtained higher light energy by increasing photosynthetic pigment contents and meanwhile improved photosynthetic phosphorylation activity by reducing the chl a/b ratio [30,31].…”
Section: Shading Increased Photosynthetic Pigment Contents Of Leaves ...supporting
confidence: 91%
“…The decrease in sucrose content after shading was more obvious than for fructose and glucose, which was consistent with reports for nectarine and wax apple [36,37]. Results of strawberry [2], maize [34,38], and soybean [39] showed that, under low light conditions, the decrease in the photosynthetic rate of leaves led to a weakening of the carbon assimilation capacity, thus seriously affecting sugar synthesis [40]. Therefore, the suppression of sucrose synthesis caused by the decreased photosynthetic rate was the main reason underlying the inhibition of the sugar accumulation in jujube leaves under shade conditions; the reduced carbohydrate accumulation then repressed vegetative growth [37].…”
Section: Shading Inhibited Sugar Accumulation In Leavessupporting
confidence: 91%
See 3 more Smart Citations